Index Card Match Boosts Math Learning by 84.2%: Index Card Match Meningkatkan Pembelajaran Matematika sebesar 84,2 - Tikasari, Della Ajeng; Setiyawati, Enik (Indonesian Journal of Education Methods Development, 2024)
This study examines the effectiveness of the Index Card Match (ICM) learning model on fifth-grade mathematics education at SDIT Ainul Yaqin. Using a pre-experimental design, 20 students were selected through purposive sampling. Test sheets were used to measure learning outcomes, and data analysis included testing for normality and calculating N-Gain scores. The results showed a significant 84.2% improvement in mathematics learning outcomes, indicating the positive impact of the ICM model on student achievement. This research contributes to understanding innovative teaching methods' efficacy in enhancing elementary mathematics education. Highlight: Effective Math Learning: Evaluating Index Card Match model in fifth-grade math education. Pre-Experimental Design: Utilizing purposive sampling to assess teaching model impact. Notable Improvement: 84.2% increase in math learning outcomes observed. Keyword: Index Card Match, Mathematics Education, Elementary School, Learning Outcomes, Innovative Teaching Methods.